2022
DOI: 10.3390/antiox11061090
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Effects of Vitamin D against Chronic Diseases: From Reduction of Lipid Peroxidation to Updated Evidence from Clinical Studies

Abstract: Background: Vitamin D exerts multiple beneficial effects in humans, including neuronal, immune, and bone homeostasis and the regulation of cardiovascular functions. Recent studies correlate vitamin D with cancer cell growth and survival, but meta-analyses on this topic are often not consistent. Methods: A systematic search of the PubMed database and the Clinical Trial Register was performed to identify all potentially relevant English-language scientific papers containing original research articles on the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 219 publications
(255 reference statements)
0
14
0
Order By: Relevance
“…Small-fiber degeneration and nociceptor sensitization are the main observed mechanisms ( 36 ). Vitamin D insufficiency or disorders of iron metabolism may have a negative impact on both innate and adaptive immunity and the development and function of the nervous system ( 35 , 37 39 ). Long-term exposure to tobacco increases pain sensitivity due to nicotinic acetylcholine receptor desensitization and neuronal plastic changes ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Small-fiber degeneration and nociceptor sensitization are the main observed mechanisms ( 36 ). Vitamin D insufficiency or disorders of iron metabolism may have a negative impact on both innate and adaptive immunity and the development and function of the nervous system ( 35 , 37 39 ). Long-term exposure to tobacco increases pain sensitivity due to nicotinic acetylcholine receptor desensitization and neuronal plastic changes ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vitamin D-enriched adults, vitamin D supplementation alone did not provide health bene ts, but vitamin D de ciency should permanently be corrected [46]. Another recent review showed that the level of biomarkers related to chronic heart metabolic diseases and cancer is signi cantly reduced by vitamin D [47]. In a survey of different countries, different diseases, and different supplements, it was found that current research disagrees the recommendation of sh oil and vitamin supplementation to weaken the risk of disease in people without nutritional de ciencies [48] and that excessive vitamin D activity can also induce vascular calci cation [49].…”
Section: Discussionmentioning
confidence: 99%
“…It is also suggested that Vit D has antioxidant properties due to its effects such as inducing the expression of various molecules in the antioxidant defense system such as GSH, GSH peroxidase, and SOD, and suppressing the expression of NADPH oxidase. However, there are few studies on its antioxidant properties, and it is not clear whether it is actually an antioxidant or pro-oxidant [14,15] Vitamin D3 (cholecalciferol) is formed by the interaction of 7-Dehydrocholesterol in the skin with sunlight. Cholecalciferol (Vitamin D3) and oral vitamin D are metabolized in the liver to 25-hydroxycholecalciferol (Calcifediol; 25(OH)D3), and this compound is then hydroxylated at the 1α-position in the kidney to convert it into the active form, 1,25-Dihydroxycholecalciferol (Calcitriol; 1,25(OH) 2 D3).…”
Section: Introductionmentioning
confidence: 99%